Problem and Solution Decomposition KSPPS Baitul Maal wa Tamwil in Maintaining the Sustainability of MSMEs - Nasrulloh, Agus Ahmad; Marlina, Lina; Nurhasanah, Elis; Joni (UPT Publikasi Ilmiah UNISBA, 2025)
This study analyzes the problems and solutions faced by KSPPS Baitul Maal wa Tamwil (BMT) in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Tasikmalaya. Using the Analytic Network Process (ANP) method and involving nine expert respondents from academic, practitioner, and regulatory backgrounds, the study identifies key internal and external challenges. The most dominant internal issue is the low quality of human resources, while the main external problem is the lack of public literacy and awareness of Islamic finance. Solutions include improving HR competence through Islamic economics training and implementing effective regulations for BMTs and the community. The study highlights the effectiveness of the ANP method in mapping issues and offers both theoretical and practical implications. Key recommendations are digital infrastructure development, stronger supervision from regulators, and collaboration with educational and religious institutions to strengthen public trust and financial literacy in the Islamic microfinance sector.